Employee Green Behavior's Impact on Sustainable Environmental Performance: Exploring The Mediating-Moderating Roles of Perceived Organizational Support and Self-Efficacy - Rezkiawan Tantawi; Near Anggreini Hesti Noviana (Jurnal Manajemen dan Kewirausahaan, 2024)
This study aims to analyze the mediating role of perceived organizational support and moderating role of self-efficacy in the influence of employee green behavior on environmental performance sustainability. The method used in the study was quantitative, involving 300 respondents. The data analysis technique utilized is path analysis to test for mediation and moderation effects. Findings of this research are perceived organizational support has no mediating role in the influence of employee green behavior on environmental performance. While self-efficacy plays a role in strengthening pro-environmental behavior in sustainable environmental performance. This research further corroborates the theory of organizational behavior, which highlights the influence of social dynamics and group norms on individual behavior. When employees observe their colleagues engaging in pro-environmental behavior, it can establish social norms within the organization and encourage the adoption of that behavior by others. The implications of these findings are that universities need to prioritize other factors that have a greater impact on improving sustainable environmental performance. For instance, external factors such as government regulations or pressure from influential stakeholders may drive organizations to adopt sustainable practices. Universities should also evaluate the strategies and policies used to enhance their environmental performance.